1993
DOI: 10.3171/jns.1993.78.5.0726
|View full text |Cite
|
Sign up to set email alerts
|

Referral bias in aneurysmal subarachnoid hemorrhage

Abstract: The objective of this study was to assess the effect of referral bias on survival in patients with subarachnoid hemorrhage (SAH). The characteristics of 49 patients with aneurysmal SAH from a single community were compared with those of 328 patients referred from outside the community, all treated in the same medical care setting. In addition, referral patients who received surgery were compared by differential survival analysis with those still awaiting surgery at Days 1 to 3, Days 4 to 10, and Days 11 to 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 32 publications
2
19
1
4
Order By: Relevance
“…This is similar to the findings from Whisnant et al, 5 who reported that 2-day survival of referral patients with subarachnoid hemorrhage was markedly better than that of local patients because the referral group did not include those who died quickly or those who were too unstable to be transferred.…”
Section: Mayo Clin Proc 2010;85(2):145-149supporting
confidence: 80%
“…This is similar to the findings from Whisnant et al, 5 who reported that 2-day survival of referral patients with subarachnoid hemorrhage was markedly better than that of local patients because the referral group did not include those who died quickly or those who were too unstable to be transferred.…”
Section: Mayo Clin Proc 2010;85(2):145-149supporting
confidence: 80%
“…Second, relatively few patients from the subgroup of 63 were admitted to our hospital within 24 hours after their initial hemorrhage, a period representing the peak interval for rebleeding from aneurysms of all sizes. [5,8] For these reasons, to minimize referral bias, [28] the reference point used to calculate the rebleeding rate was the time of admission to our institution (Day 0) rather than the time of the initial hemorrhage. As a result, our findings reflect the expected rate of rebleeding after admission among patients suffering ruptured giant aneurysms who were referred to experienced neurosurgeons at medical centers similar to our own.…”
Section: Discussionmentioning
confidence: 99%
“…Data from this subgroup were used to calculate the incidence of rebleeding during the first 2 weeks after admission to our hospital, and life table methods were used to estimate cumulative frequency of rebleeding, with patients being excluded if they died of another cause during the first 2 weeks after admission. To minimize inaccuracy caused by referral bias, [28] the time of admission to our institution rather than the time of initial hemorrhage was used as the reference point (Day 0) in estimating the rebleeding rate.…”
Section: Rebleeding Ratementioning
confidence: 99%
“…In community-based studies, if study covers a large geographic region, a number of SAH patients, especially those in the outlying areas, may never reach the hospital and die before receiving medical care or may be treated at hospital of other district 14,24) . On the contrary, if populations are too small, it is difficult to assess accurate incidence rates 14,17,23) .…”
Section: Discussionmentioning
confidence: 99%